FAMILY HISTORY, KNOWLEDGE, AND RESTING PATTERNS ASSOCIATED WITH HYPERTENSION: CASE-CONTROL STUDY: Riwayat Keluarga, Pengetahuan, dan Pola Istirahat terkait dengan Hipertensi (Studi Case-Control) - Rizqiyah Syafitri, Nadia; Qurniyawati, Eny; Nityasani, Renaningtyas; Ssekalembe, Geofrey (Jurnal Berkala Epidemiologi, 2025)
Background: Non-communicable diseases are the leading cause of death worldwide, responsible for approximately 75% of global mortality. Hypertension, a significant contributor to NCD-related deaths, affects an estimated 1.28 billion adults globally and is often referred to as "The Silent Killer." The increasing prevalence of NCDs, including hypertension, poses significant challenges to the global health system. In Ponorogo Regency, hypertension cases surged from 41,841 in 2021 to 126,668 cases in 2023. Analyzing the risk factors of hypertension is essential to mitigate its health impact on the community. Purpose: To analyze the risk factors of hypertension cases in the Plosojenar Village, Ponorogo Regency community. Methods: This quantitative study employed a case-control design with 154 participants. The case group comprised 77 individuals with hypertension, and the control group included 77 non-hypertensive individuals, selected through random sampling at a 1:1 ratio. Data were collected from January to April 2024 using questionnaires. Bivariate analysis was conducted using Chi-square and Fisher’s tests. Results: This study found a significant association between family history OR 13.67 (95%CI = 5.63 - 39.17); p = 0.00, level of knowledge OR 26.25 (95%CI = 3.96 - 1.11); p = 0.05, and rest habits OR 0.18 (95%CI = 0.03 - 0.70); p = 0.08 to hypertension cases. This study also showed no significant relationship between attitude OR 0.88 (95%CI = 0.32 - 2.37); p = 1 with hypertension cases. Conclusion: Family history, knowledge level, and rest habits are significantly associated with hypertension. Targeted interventions addressing these factors may help reduce hypertension cases.